The Development and Validation of the Psychological Needs of Cancer Patients Scale - Chen, Yao; Lin, Fangyan; Wang, Bo; Tang, Yung-lung; Li, Jun; Xiong, Lin (Frontiers in Psychology, 2021)
In the present research, the Psychological Needs of Cancer Patients Scale (PNCPS) was developed and validated. Based on Group 1 (400 cancer patients), the exploratory factor analysis identified a 23-item scale with six factors: value and esteem (5 items, i.e., reconsider the meaning and purpose of life), independence and control (6 items, i.e., private space), mental car (3 items, i.e., vent negative emotions), disease care (3 items, i.e., acquire knowledges about disease), belonging and companionship (3 items, i.e., spend more time at home), and security (3 items, i.e., living conditions be better). The structure identified with Group 1 was further tested, based on Group 2 (199 cancer patients), for reliability and validity. The results showed that PNCPS has a clear factor structure and good psychometric characteristics. By taking into account the cultural background of Chinese patients, this scale will advance the study of the psychological needs of those with malignant tumors, and thus has a certain reference value for other countries.